2010
DOI: 10.1016/j.jsbmb.2010.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear vitamin D receptor controls the expression of genes encoding factors which feed the “Fountain of Youth” to mediate healthful aging

Abstract: The nuclear vitamin D receptor (VDR) binds 1,25-dihydroxyvitamin D 3 (1,25D), its high affinity renal endocrine ligand, to signal intestinal calcium and phosphate absorption plus bone remodeling, generating a mineralized skeleton free of rickets/osteomalacia with a reduced risk of osteoporotic fractures. 1,25D/VDR signaling regulates the expression of TRPV6, BGP, SPP1, LRP5, RANKL and OPG, while achieving feedback control of mineral ions to prevent age-related ectopic calcification by governing CYP24A1, PTH, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 101 publications
4
127
0
2
Order By: Relevance
“…Previous studies have demonstrated an interaction between the VDR and ␤-catenin that is dependent upon 1,25-dihydroxyvitamin D (18,25,35). Although the liganded VDR attenuates canonical Wnt signaling (35,36), ␤-catenin has been shown to be a ligand-dependent coactivator of the VDR (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated an interaction between the VDR and ␤-catenin that is dependent upon 1,25-dihydroxyvitamin D (18,25,35). Although the liganded VDR attenuates canonical Wnt signaling (35,36), ␤-catenin has been shown to be a ligand-dependent coactivator of the VDR (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although the liganded VDR attenuates canonical Wnt signaling (35,36), ␤-catenin has been shown to be a ligand-dependent coactivator of the VDR (18). Traditional nuclear receptor coactivators are recruited to the VDR in response to a conformational change that occurs upon ligand binding, rendering the AF2 domain accessible for interactions with these cofactors (37).…”
Section: Discussionmentioning
confidence: 99%
“…[29] The VDR is a member of the thyroid hormone and retinoic acid receptor subfamily of nuclear hormone receptors that heterodimerizes with retinoid X receptor isoforms to regulate the expression of genes encoding factors which, in a variety of cell types, control functions such as proliferation, differentiation, metabolism, ion transport, and apoptosis, etc. [46] Vitamin D and immune system Erectile dysfunction is associated with an incremental inflammatory activation and inflammation plays an important pathophysiological role in both ED and CV diseases. It has been extensively debated that inflammation can exert a detrimental effect on the CV system via two pathways ie.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
“…However, 1,25(OH) 2 D 3 /VDR signaling is also involved in immunity regulation, detoxification of xenobiotics, antimicrobial defense, anti-inflammatory and anticancer effects, and cardiovascular protection (420). VDR also activates the mammalian hair cycle, exemplifying an additional VDR function that promotes healthy aging (174). In addition to these multiple actions, the protective vitamin D effects involve a suppressive action on RAS (see The KLOTHO-Vitamin D-RAS Connection and Fig.…”
Section: (See the Role Of Sirtuins In Cr)mentioning
confidence: 99%